Nanogel-Mediated antigen delivery: Biocompatibility, immunogenicity, and potential for tailored vaccine design across species - Soriano Perez, María Laura (2024)
Nanotechnology has emerged as a promising avenue for enhancing the efficacy of vaccine delivery systems. This study investigates the utilization of nanogels as carriers for the model antigen ovalbumin, with a focus on in vivo assessments in equine and murine models. Nanogels, owing to their biocompatibility and tunable physicochemical properties, offer a versatile platform for efficient antigen encapsulation and controlled release. The encapsulation efficiency and physicochemical characteristics of ovalbumin-loaded nanogels were comprehensively characterized. In vitro biocompatibility was evaluated, finding excellent properties of these nanogels. In vivo evaluations were conducted on both equine and murine subjects, assessing immunogenicity through antibody and splenic cell response. Furthermore, the study propose the potential use of nanogels in tailoring immune responses through the modulation of antigen release kinetics. The results obtained in the in vitro assays showed an increase in the uptake of nanogels by APCs compared to free antigen (OVA). In mice, an absence of inflammatory response in the inoculation site was observed, without systemic damage in the evaluated organs. In addition, non-significant humoral response was found nor cellular proliferation and proinflammatory cytokine production, compared with a traditional adjuvant as aluminum hydroxide, in both animal models. These findings allow further insights into nanogel-based delivery systems and offer valuable insights into their application in various animal models. In conclusion, this research establishes the utility of nanogels as effective carriers for antigens-based vaccines, with interesting biocompatibility properties and highly taken affinity by antigen-presenting cells, without inducing inflammation at the injection site. The study underscores the potential of nanogel technology in revolutionizing vaccine design and highlights the importance of tailored approaches for diverse target species.